BATCH SCHEDULING FOR A SINGLE ITEM FLOW SHOP WHICH CONSIDERS MACHINE DETERIORATION TO MINIMIZE TOTAL ACTUAL FLOW TIME - NORIZKI( NIM : 23411029 ); Pemimbing : Prof. Dr. Ir. Abdul Hakim Halim, JULFIKAR
This research addresses flow shop batch scheduling problem which considers machine deterioration. The processing time of parts in a batch scheduled at a position is shorter than that at the previous position in a backward scheduling approach. The objective is to minimize total actual flow time defined as total interval between respective arrival times of all parts in all batches and their common due date. Decision variables are the number of batches (N), batch sizes (Q) and sequence of the resulting batches on m-machine. The solution method is solved by relaxing variable N to be a parameter, started from N = 1 and increased one by one iteratively until a stopping rule is satisfied. The chosen solution is given by the solution that gives the smallest total actual flow time between other solutions from all iterations. Numerical experiments shows that the proposed method can be used to solve the discussed problem.